Benign proliferative pilomatricoma over sternum: a rare case - Harsha, Muvva Sri; E., Rajesh Goud; Jakkula, Srikanth (International Surgery Journal, 2018)
Pilomatricoma is a benign, uncommon, subcutaneous tumor arising from the outer root sheath cell or hair matrix cells. Pilomatrixoma, benign calcifying epithelioma of Malherbe, trichomatricoma are synonyms for pilomatricoma. They occur mostly on head, neck and upper limb extremities. Histologically they classically consist of peripheral basiloid cells and central enucleated ghost or shadow cells. Malignant changes are rare in pilomatricomas. However, the proliferative variety is aggressive and considered to be precursor of malignancy. Here we present a case of benign proliferative pilomatricoma over sternum for which the patient underwent wide local excision, diagnosis was later confirmed by histopathological examination. We have not come across any cases of pilomatricoma occurring over sternum in literature.